Effect of Molecular Weight and Processing Additive on the Performance of Low Bandgap Polymer Solar Cells - 赵晓礼 唐浩为 杨大磊 李慧 徐文涛 尹丽 杨小牛 (Chinese journal of chemistry, 2012)
In this work, we synthesized a low bandgap polymer polysilole（-2,6-diyl-alt-5-octylthieno[3,4-c]pyrrole-4,6- dione） （PDTSTPD） with different molecular weights （Mn）. The devices based on PDTSTPD/PC71BM composite are prepared and the dependence of power conversion efficiency （PCE） of the devices on the M,1 of conjugated poly- mers is addressed. We found the hole mobility of PDTSTPD is dependent on the Mn of the polymer, which should be the main reason contributing to the drastic difference of device performance, i.e. the PCE of the device using 10 kDa polymer is only 0.52%, in contrast to 2.3% for 24 kDa polymer device. This PCE data is then further improved to 5.0% via using 1,8-diiodoctane as processing additive to achieve an optimized morphology for the photoactive layer with an appropriate length-scale of phase separation for both exciton dissociation and charge transportation.